Karakteristik Minuman Probiotik Sari Ubi Kayu dari Kultur Bakteri Lactobacillus acidophilus dan Streptococcus thermophilus - Yulia, Nunung; Wibowo, Adi; Kosasih, Eva Dania (Jurnal Kefarmasian Indonesia, 2020)
Functional foods are food that consumed, as usual, has a physiological effect and can reduce the effect of chronic disease. One of them is probiotic beverages. Probiotic beverages that have been widely known overtime was produced by a dairy house. This product could have been expensive due to the cost of raw materials. The alternative raw material such as the use of extracted cassava juice may reduce the price of the final product. The aims of this research were to study the effects of culture comparison between characteristics of the probiotic beverage from cassava juice, and get the best culture comparison that produces the best probiotic characteristics of the lactic beverage fermentation from cassava juice. This research applied qualitative experiment method in Lactobacillus acidophilus and Streptococcus thermophiles as an inoculum evaluated. Serial in culture ratio respectively 20:50; 30:50; 40:50; and 50:50. The observed research were pH value, viscosity, total lactic acid bacteria (LAB) and activities test against bacteria Escherichia coli. The result showed that the best culture comparison qualified as probiotics criteria was 50:50. It was having pH value 4,1; viscosity 0,706 g/mL; total LAB 2,1x106 cfu/mL and activity bacteria Escherichia coli was 5,3 mm.